ISO 14001 step by step : a practical guide - Sadiq, Naeem; Khan, Asif Hayat (IT Governance Publishing Limited, 2019)
"This book provides practical advice on how to achieve compliance with ISO 14001:2015, the international standard for an EMS (environmental management system). With an EMS certified to ISO 14001, you can improve the efficiency of your business operations and fulfil compliance obligations, while reassuring your employees, clients and other stakeholders that you are monitoring your environmental impact."--